Does subjective assessment of dialyzer appearance reflect dialyzer performance in online hemodiafiltration? - Matos, J. F.; Pinto, B.; Félix, C.; Carvalho, H.; Ponce, P.; Peralta, R. (Hemodialysis International, 2020)
Introduction:In post-dilution online hemodiafiltration, a very thin balance subsists in preventingcoagulation of the extracorporeal circuit (ECC) during treatment and bleeding in the patient, con-cerning dialyzer status and anticoagulation dose.The aim of this study was to assess whether there are clinical outcome differences between thevisual aspect of the dialyzer’s status in terms of clottedfibers at end of dialysis treatments, single-pool urea kinetic modeling (spKt/V) and substitution volume (SubsVol).Methods:It is a multicenter, descriptive-correlational study, involving 2829 patients during April2016. Previous training was given to the Nursing staff to evaluate and classify both the dialyzer’sand the venous chamber’s appearance of the ECC venous line. Registration was performed at bed-side immediately after the patient disconnection.Findings and discussion:Mean age was 68.96 years (SD= 13.75), 60.8% were men. The averagehematocrit was 33.91% (SD= 3.45%). The average dry weight was 68.53 kg (SD= 13.27 kg). Meanunfractioned heparin (UFH) dose was 58.13 IU/kg. Only 32.4% of the patients had a clean dialyzerat the end of treatment. 19.4% of patientsfinished the treatment with more than 10% of clottedfibers. Patients with no residual blood (clean, 32.4%) presented a higher UFH dose (66.32 IU/kg)compared to overall average dose. UFH dose had a significant effect on dialyzer status. There weresignificant differences in average ofspKt/V and SubsVol between the category clean and the othercategories of dialyzer’s status.Evaluating the dialyzer status represents an excellent opportunity to help the physicians to estab-lish an ideal heparin dose. Only the categorycleanis significant to achieve the target. The nursingstaff, by classifying the ECC appearance at patient’s bedside and recording it in a centralized database, can be a major contributor to achieve an individualized and optimal UFH dose and subsequently better patient outcomes.